Hyperthermia induces the ER stress pathway. - Xu Xu; Sounak Gupta; Wenli Hu; Barbara C McGrath; Douglas R Cavener (PLoS ONE, 2011)
The ER chaperone GRP78/BiP is a homolog of the Hsp70 family of heat shock proteins, yet GRP78/BiP is not induced by heat shock but instead by ER stress. However, previous studies had not considered more physiologically relevant temperature elevation associated with febrile hyperthermia. In this report we examine the response of GRP78/BiP and other components of the ER stress pathway in cells exposed to 40°C.AD293 cells were exposed to 43°C heat shock to confirm inhibition of the ER stress response genes. Five mammalian cell types, including AD293 cells, were then exposed to 40°C hyperthermia for various time periods and induction of the ER stress pathway was assessed.The inhibition of the ER stress pathway by heat shock (43°C) was confirmed. In contrast cells subjected to more mild temperature elevation (40°C) showed either a partial or full ER stress pathway induction as determined by downstream targets of the three arms of the ER stress pathway as well as a heat shock response. Cells deficient for Perk or Gcn2 exhibit great sensitivity to ER stress induction by hyperthermia.The ER stress pathway is induced partially or fully as a consequence of hyperthermia in parallel with induction of Hsp70. These findings suggest that the ER and cytoplasm of cells contain parallel pathways to coordinately regulate adaptation to febrile hyperthermia associated with disease or infection.